ANALISIS PENGGUNAAN TRADING SYSTEM TEKNIKAL COUNTER TREND dan TREND FOLLOWING TERHADAP TRADING RETURNS pada TRANSAKSI FOREIGN EXCHANGE ONLINE - Rahadian Dimas Dwi Sandra (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study is to find out how the result of trading activities in eight major currencies using expert advisors that apply trend following trading system and counter trend trading system affect the investment return in foreign exchange online. There are two points that we compare wich is return and risk, using the descriptive analysis and independent sample t-test. We found that trend following trading system is more profitable and safer than counter trend trading system, where trend following trading system can make a profit return on all eight pair currencies studied and also lower standard deviation than counter trend trading system, where counter trend trading system can make profit only on five major pair currencies .Keywords: Counter Trend, Trend Following, Expert Advisor